Mechanical and thermal properties of natural fibre based hybrid composites: a review - Dashtizadeh, Zahra; Abdan, Khalina; Jawaid, Mohammad; Khan, Mohd Asim; Behmanesh, Mohammad; Dashtizadeh, Masoud; Cardona, Francisco; Ishak, Mohamad Ridzwan (Universiti Putra Malaysia Press, 2017)
Environmental issues have motivated researchers to replace synthetic fibres with natural fibres in the fabrication of polymer composites. However, natural fibres demonstrate weak mechanical or thermal properties which limit their different applications. Researchers have suggested fabrication of hybrid composites in order to improve the mechanical and thermal properties of natural fibre-based composites. Hybrid composites are made up by two or more fibres in one matrix or two polymer blends and with one natural fibre reinforcement. By hybridising one natural fibre with another natural fibre/synthetic fibre in one matrix, the resulting composite is a unique product (hybrid composites) that displays better mechanical and thermal properties in comparison with individual fibre-reinforced polymer composites. The advantages of developing hybrid composites are that they are more reliable for different applications and more environmental friendly. In this review paper, we present some recently published works related to mechanical and thermal properties of natural/natural fibres, and natural/synthetic fibre-based hybrid composites. Hybrid composites are one of the emerging fields in material science which has attracted attention for their different engineering applications.